Potential of Mahang (Macaranga Gigantea) wood as a core material in sandwich composite. - Noor Sharina Azrin Zakari (2018)
Mahang wood (Macaranga) is one of the lesser known wood species (LKS) available in Malaysia. It is one of those underutilized fast-growing pioneering species. Categorized as a light hardwood timber, Mahang wood is considered as a viable alternative to be utilized in the construction of sandwich composite. Typically, the core of sandwich composite is made of Balsa wood. This study aims to investigate the microstructure, physical and mechanical properties of Mahang wood, core and sandwich composite in an attempt to employ this underutilized species as a core in sandwich composite. Samples were analysed for physical and mechanical strength while the microstructure of Mahang wood was observed under scanning electron microscope (SEM) for anatomical analysis. Density of wood was evaluated by considering the oven dried mass and green volume of the specimens. Immersion of sample in tap water was carried out for determination of water absorption properties by considering the mass change after period of immersion. Several American Society for Testing and Materials (ASTM) standards were adopted to establish a valid procedure to conduct the mechanical testing for wood, core and sandwich composite. The tests were conducted by varying Mahang wood portions and grain orientation. The results obtained were compared with Balsa wood. Results show that density of Mahang wood falls within the range of Balsa wood density and sandwich composite is considered as lightweight panel with density less than 500 kg/m3. Water absorption test revealed the water absorption properties of Mahang and core were less than Balsa wood which signifies that water resistant property of Mahang is better than Balsa wood. Mechanical properties of Mahang wood emerged considerably high. Average tensile strength of bottom and middle part of Mahang trunk are 405.39 MPa and 337.22 MPa. The effects of grain orientation and wood portions of Mahang trunk on the performance of sandwich composite were investigated. Physical properties and flexural strength of sandwich composite and its core do not depend on the grain orientation. Only tensile and compression strength have been significantly affected by grain orientation. Wood portions do influence the mechanical strength of sandwich composite. Wood density varies axially and this translates into variation of mechanical strength. The relevance of Mahang wood as a core in sandwich composites is clearly supported by the analysis of variance (ANOVA). The most significant finding in this study is that Mahang wood seems to be a viable alternative to be used as a core in sandwich composite as it possesses almost the same properties as Balsa wood.